Inquisitore e Vescovo a Malta: Conflitti e competenze dai documenti della Corte di Napoli - Romano, Ciro (The Roman Inquisition in Malta and elsewhere, 2017)
Copious correspondence between the King of Naples and the Order of St John survive in the State Archive of Naples. These offer unique insights into the skills and the limits of the Inquisitor of Malta in respect to the prerogatives of the King, the Order of St John, or the local Bishop. This study will concentrate on 18th-century correspondence to analyse the relationship between the King of Naples and Sicily, and the Inquisitor: their conflicts, their skills and mutual areas of jurisdiction.